GAP IMPLEMENTASI KEBIJAKAN BINA KELUARGA TKI DI KABUPATEN MALANG - Ani Puspawati (Wacana Publik, 2018)
The Indonesian Migrant Workers' (TKI) Family Development Policy aims to solve TKI family problems in the fields of economic empowerment, family security and child protection. The study was conducted in Tlogosari Village, Donomulyo District, Malang Regency. This type of research is qualitative. The implementation was unsuccessful because it stopped at the preparation stage. In this study describes the implementation gap that occurs.